2021
DOI: 10.5209/clac.76714
|View full text |Cite
|
Sign up to set email alerts
|

An SLA-Informed and Cognitive Linguistic Approach to the Teaching of L2 Catalan Tense-Aspect

Abstract: This article explores the relationship between second language acquisition and language teaching presenting the design of a teaching sequence on past tenses that integrates the results of research on tense and aspect in a second language (the Aspect and Discourse Hypotheses and Input processing instruction). By implementing the principles of cognitive linguistics, the article presents the design of activities to teach the meanings of perfective, imperfective, and perfect morphology with the introduction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Similar to Soulé and Granda's (2015) progression of instruction for Spanish, Comajoan-Colomé and Llop Naya (2021), working with L2 Catalan, introduced nonprototypical combinations of lexical category, grounding, and morphology earlier (at the A2 level), partly because their learners already knew other Romance languages. Comajoan-Colomé and Llop Naya (2021) advocated for an SLA-informed approach to the teaching of L2 Catalan tense-aspect based on cognitive linguistics and included a detailed sequence of classroom activities for the A1-B1 levels that took into account lexicoaspectual categories and narrative grounding. For instance, for the introduction of grounding, they designed an activity in which learners were asked to say what they saw in Image 1 in Figure 3.…”
Section: The Reviewsmentioning
confidence: 80%
See 2 more Smart Citations
“…Similar to Soulé and Granda's (2015) progression of instruction for Spanish, Comajoan-Colomé and Llop Naya (2021), working with L2 Catalan, introduced nonprototypical combinations of lexical category, grounding, and morphology earlier (at the A2 level), partly because their learners already knew other Romance languages. Comajoan-Colomé and Llop Naya (2021) advocated for an SLA-informed approach to the teaching of L2 Catalan tense-aspect based on cognitive linguistics and included a detailed sequence of classroom activities for the A1-B1 levels that took into account lexicoaspectual categories and narrative grounding. For instance, for the introduction of grounding, they designed an activity in which learners were asked to say what they saw in Image 1 in Figure 3.…”
Section: The Reviewsmentioning
confidence: 80%
“…Beginning in the 2000s, there was an increase in interest in cognitive linguistics and its application to the teaching of L2 grammar, and more specifically to the teaching of tense-aspect in different L2s (cf. applied cognitive linguistics, Achard, 2008;Castañeda, 2014;Comajoan-Colomé & Llop Naya, 2021;Ibarretxe-Antuñano et al, 2019;Kermer, 2016;Niemeier, 2017;Pütz, 2007;Reif, 2012;Samu, 2020;Tyler, 2012). The cognitive pedagogical proposals included in this review adopt a cognitive framework to teach grammar that centers around motivation for grammar (i.e., emergence of grammar out of communicative needs), speaker perspective as the main factor in the choice of perfective or imperfective (as opposed to rules of thumb), and prototypical and non-prototypical meanings of perfective/imperfective morphology and meanings.…”
Section: Language Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…The cognitive linguistics branch of SLA has shown that usage-based approaches to language hold great potential for a pedagogical application, but it is still a developing field and extensive studies remain sparse (cf. Bielak & Pawlak, 2011;Comajoan-Colomé & Llop Naya, 2021;Kermer, 2016 for tense and aspect). Nonetheless, methods, tools, and strategies are being developed for the pedagogical application of cognitive linguistics and construction grammar and as Gilquin (2022) shows, pedagogical applications that combine cognitive linguistics and corpus linguistics are very promising.…”
Section: B Ta Learning: Aspect Tense Associationsmentioning
confidence: 99%
“…El treball de Segura-Llopes (2016) sobre el pronom en i la gramàtica de construccions és el punt de partida d'aquest estudi, com veurem tot seguit. Però també han sorgit altres propostes com ara sobre l'adquisició i l'ensenyament del temps de passat en un model cognitiu, de Comajoan-Colomé & Llop (2021). Segura-Llopes (2016) va establir un model d'aplicació per a la construcció en-partitiva («en tinc dos») i va dur a terme un experiment en adults amb resultats que van mostrar que el grup construccional adquiria amb més èxit la construcció partitiva en contextos d'ús que el grup tradicional.…”
Section: Introduccióunclassified